The location of immigrants at retirement: stay/return or 'va-et-vient' - Augustin de Coulon; François-Charles Wolff (Institute for the Study of Labor (IZA), 2006)
In this paper, we investigate the location choice of immigrants when retiring. In a context where labour considerations no longer matter, the location decisions are expected to depend not only on a comparison of standard-of-living between the origin and host countries, but should also be affected by the strength of family relationships. Assuming that migrants derive some satisfaction from contact and visits with other family members, we suggest that migrants may choose a third type of migration move beyond the standard stay/return decision called the 'va-et-vient', where individuals choose to share their time across the host and the origin country. In the empirical analysis, we investigate the determinants of the location intention when retiring using a recent data set on migrants currently living in France. We find that the migrant's choice is significantly related to the location of other family members and that those determinants vary with respect to the different preferred choices.
Keywords: J26; O15; R23; 330; return migration; retirement; family interactions